The Rapid Uptake of Digital Technologies at Domestic Violence and Sexual Assault Organizations During the COVID-19 Pandemic. (April 2023) - Storer, Heather L.; Nyerges, Eva X.
Emerging evidence suggests that the COVID-19 pandemic disproportionately impacted survivors of domestic violence and sexual assault (DV/SA). This research note explores DV/SA service providers' ( n  = 20) perceptions of how their organizations responded to the pandemic. Results of a thematic content analysis indicated that survivors were adversely affected by sheltering with abusive partners and by external environmental conditions. Organizations responded to shifting community needs by adapting face-to-face services to virtual formats and revising pre pandemic safety planning protocols. School-based prevention programming required significant adjustments. Therefore, the pandemic catalyzed the integration and optimization of emerging technologies and provided opportunities for organizational innovation.